The Intersectionality of Gender and Slavery: Paul’s Social Creativity within an Unchangeable System - Seal, Darlene M. (Journal for the study of the New Testament, 2025)
Roman statuary of colonized peoples depicted as personified and feminized figures indicates that slavery was backed by the military might of Rome and thus was an unchangeable system. The reality that many slaves were conquered peoples justifies reading Paul’s exhortation to ‘remain as you are’ in 1 Cor. 7.17–24 in light of both the intersection of gender and slavery for women slaves subject to the sexual whims of male masters and their double marginalization by imperial propaganda. Given the impossibility of changing the slavery system, Paul sketches an ideological resistance when he portrays Christ as the ultimate Master but one who first suffered and died as a slave, that is, as one with no bodily autonomy. Thus Paul practices social creativity by offering a Christocentric counternarrative that provides the ideological basis for equality among Jesus-followers even though social inequity outside the communities remains an unavoidable reality.